Functional English Design for Domestic Migrant Workers - Hermayawati Hermayawati (Universitas Ahmad Dahlan, 2018)
This paper aimed at: (1) describing the content of Functional English Design (FED) materials and (2) describing the appropriateness of the FEDas the English training materials for the migrant workers' candidates (MWC). This study used ADDIE (Analysing, Designing, Developing, Implementing and Evaluating) model involving totally 200 MWC in the 4 PPTKIS (namely authorized private boards in which duties serves the Indonesian workers' placement and protection abroad).The data were taken from the documentation, the traineesâ€™ English training achievements using the FED and peer-debriefing. The gathered data was analyzed using: Content Analysis and Mean-difference computation of the trainees' test results descriptively. This study found: (1) the content of the FEDthat developedâ€œImparting and seeking factual informationâ€ with â€œMinimumâ€“adequate language Functionsâ€ was matched with the trainees needs and (2) the FED was appropriate to use as an alternative English materials since it was designed based on the result of needs analysis beside the test result in significant improvement i.e. the Mean Difference of the oral pre and post-test was 2.25 within the scoring standard scale of 0-10, while the Md of the written pre-post-test was 13.35 within the scoring standard scale of 0-100. Besides, the peers debriefing stated that the FED was recommended for use in the 4 investigated PPTKIS.